Quantum dots-templated growth of strain-relaxed GaN on a c-plane sapphire by radio-frequency molecular beam epitaxy - 郭浩民 文龙 赵志飞 步绍姜 李新化 王玉琦 (Chinese physics B, 2012)
We investigated the quantum dots-templated growth of a（0001） GaN film on a c-plane sapphire substrate.The growth was carried out in a radio-frequency molecular beam epitaxy system.The enlargement and coalescence of grains on the GaN quantum dots template was observed in the atom force microscopy images,as well as the more ideal surface morphology of the GaN epitaxial film on the quantum dots template compared with the one on the AlN buffer.The Ga polarity was confirmed by the reflected high energy electron diffraction patterns and the Raman spectra.The significant strain relaxation in the quantum dots-templated GaN film was calculated based on the Raman spectra and the X-ray rocking curves.Meanwhile,the threading dislocation density in the quantum dots-templated film was estimated to be 7.1×107cm-2,which was significantly suppressed compared with that of the AlN-buffered GaN film.The roomtemperature Hall measurement showed an electron mobility of up to 1860cm2 /V·s in the two-dimensional electron gas at the interface of the Al 0.25Ga0.75 N/GaN heterojunction.